FROM SHARIA POLITICS TO POLITICAL SHARIA: Towards Democratic Elections Based on the Qur'an - Al-Banjari, Husin M (Aliansi, 2024)
Ibn Taimiyah (1263-1328) in his work as-Siyasah asy-Syar'iah has marked Islamic Politics with "just siyasa" or "pious government," where his political thinking is based on two epistemes contained in Surah An-Nisa Verses 58-59 of the Qur'an. The two epistemes are (1) to convey your amana to its expert and (2) when you make legal decisions between people, you should decide justly. By using qualitative methods, more precisely the approach of critical philosophy, then the same research data -Surah An-Nisa Verses 58-59 of the Qur'an- in this article the basic paradigm will be shifted from as-Siyasah asy-Syar'iah (Sharia Politics) to the opposite direction asy-Syar'iah as-Siyasiyah (Political Sharia), that means changing the analytical perspective from the study of Government Science to the study of Political Science. This approach leads to a surprising conclusion, that the basic epistemological meaning of the diction "politics" in the Qur'an refers to electoral politics rather than appointment politics. This is a valuable finding to state with academic proof, that Islam is not only compatible with democracy, but Islam is the mother of democracy. With this finding, this article does not hesitate to propose the concept of democratic elections based on the Qur'an; there is no obligation to implement Islamic law, this is a universal and genuine political concept that allows or even recommends all existing government systems today to implement it, regardless of whether they are capitalist, communist, Confucian, or other ideologies, and without questioning how many Muslims there are in the country: majority, balanced, minority, or none at all.